Challenges in diagnosing and treating chronic exertional compartment syndrome: perspective from a student nurse with lower extremity pain - Marbel, Madelyne; Knoerl, Robert (Frontiers in Physiology, 2025)
Chronic Exertional Compartment Syndrome (CECS) is an uncommon yet debilitating condition that causes activity-induced pain due to increased pressure within muscle compartments. While typically diagnosed through dynamic intercompartmental pressure testing, CECS presents significant diagnostic challenges due to overlapping symptoms with other musculoskeletal conditions. This first-person narrative describes a 23-month journey through inconclusive imaging, multiple rounds of physical therapy, and pressure testing that met, but was ultimately dismissed despite established CECS diagnostic criteria. The case underscores the mismatch that can occur between objective findings and clinical interpretation, particularly when symptoms affect atypical compartments. With surgery ruled out and conservative treatments offering minimal relief, the experience reveals critical gaps in diagnostic consistency, clinician-patient communication, and care pathways for individuals whose symptoms reside in a diagnostic gray zone. This narrative calls for more nuanced application of diagnostic tools, greater attention to patient-reported symptoms, and improved support systems for those navigating prolonged diagnostic uncertainty.